The Dynamic Role of Moslem in Building Indonesia as a Nation-State - Ricardi S. Adnan (Indonesian Center for Religion and Society Studies (InTReSt), 2023)
This study figures out the historical journey of the Indonesian nation which is full of its own dynamics is marked by the prominent role of Moslem figures in fighting for and maintaining national unity. The socio-cultural diversity is vital capital as well as a big challenge for Indonesia in building a nation-state. For more than seventy years this pluralistic society has been united by one state ideology, namely